Thrombolysis and reperfusion: advanced understanding of early management strategies in acute ischemic stroke. (May 2014) - Zhang, Dong; Zou, Xinying; Sy, Christopher; Qin, Haiqiang; Wang, Yilong; Liao, Xiaoling; Liu, Liping
Abstract : Currently, intravenous (IV) thrombolysis within 3 hours from stroke onset is the only approved treatment in acute ischemic stroke (AIS). Although effective, the definition of therapeutic time window and appropriate patient selection still remains controversial. Notably, early endovascular treatment strategies may serve as an adjunct therapy for time window extension in AIS. In this article, we review the safety and efficacy of IV thrombolysis in AIS as it pertains to the optimal time window, the selection of eligible patients, and in combination with endovascular treatment. Combined clinical application of IV thrombolysis and endovascular therapy may improve the therapeutic outcomes for AIS patients.